Endothelial dysfunction and vascular-platelet hemostasis in patients with type 2 diabetes mellitus and hypertension with poor glycemic compensation. - Pertseva, N. O. (Морфологія / Morphologia / Morfologìâ, 2017)
Background. Many questions about the relationship between endothelial dysfunction and morphological substrate of hemostasis damage that occur during the progress of type 2 diabetes mellitus and arterial hypertension require clarification and further advance. Objective. The aim of this study is to determine the relationships between endothelial dysfunction, the degree of renal function damage, lipidemic profile and morphological changes of vascular-platelet hemostasis in patients with poor compensation of type 2 diabetes mellitus and arterial hypertension. Methods. In 78 patients with poor glycemic compensation using clinical, laboratory, morphological methods and correlational analysis were identified association between endothelial dysfunction, degree of renal function damage, lipidemic profile and morphological changes of vascular-platelet hemostasis. Results. In patients with poor glycemic control content of unactivated platelets had high power feedback with all three studied markers of endothelial dysfunction ranging from r=-0,74 to r=-0,84 (p<0,05), and set the reliable correlation with the majority of clinical and laboratory parameters except diastolic blood pressure levels, hemoglobin and high density lipoprotein cholesterol. Initially, the study determined a significant increase in direct interdependence between the degree of platelet aggregation and levels of glycated hemoglobin (r=+0,86), endothelin-1 (r=+0,95), von Willebrand factor (r=+0,91) and thrombomodulin (r=+0,88). Also share aggregated platelets greatly strengthened correlation with the majority of renal function parameters (strongest of them – with microalbuminuria (r=+0,81)) and established significant direct correlation with parameters of atherogenic dyslipidemia triad. Similar in direction and structure of the correlation matrix revealed when calculating the correlation coefficient of linear relative degranulated and activated platelets forms. In patients with poor compensation of hyperglycemia the density of packing of the alpha- and delta-granules of platelets were in secure communication with reversible levels of HbA1c, systolic blood pressure, endothelin-1, triglycerides. Patients had inverse correlation of alpha-granules and delta-granules with von Willebrand factor concentrations (r=-0,66 and r=-0,53 respectively; p<0,05) and thrombomodulin (r=-0,70 and r=-0,78 respectively; p<0,05), and amplified power relations with low density lipoprotein cholesterol. Packing density of mitochondria, despite the significantly reduced levels compared with controls, not establish significant correlations with most of the clinical and laboratory parameters. Only the level of endothelin-1 were found inverse correlation (r=-0,62). Conclusion. It has been established that in the poor glycemic control by a significant strengthening relationships between indicators of endothelial dysfunction and damaged platelet hemostasis formed extremely dense correlations of ultrastructural characteristics of platelets with clinical and laboratory signs of nephropathic and dyslipidemic changes.